Pengelolaan Hasil Laut Berbasis Komunitas Nelayan di Pulau Sumbawa untuk Mendukung Pariwisata Kuliner Lokal - Ardana, Taufik; Zulmi, Rizal (UNITY: Journal of Community Service, 2025)
Community-based marine resource management among fishermen in Sumbawa Island is a key strategy to support local culinary tourism. This article aims to analyze how community-based approaches can enhance the added value of marine products and strengthen the appeal of culinary tourism in the region. The methods include interviews with local fishermen, field observations, and secondary data analysis from tourism and fisheries reports. The findings indicate that through community-based management, such as the establishment of fishermen's cooperatives, training on seafood processing, and collaboration with the tourism sector, economic and social potential can be improved. This strategy also promotes the sustainability of marine ecosystems. Therefore, community-based marine resource management among fishermen in Sumbawa Island serves as a replicable model for supporting sustainable tourism in other regions.